Obwieszczenie : w miesiącu listopadzie 1947 płacimy [...]. (Tczew : [s.n.], 1947)
Owbieszczenie dot. cen m.in. mleka, tłuszczu.
Keywords: Ceny -- Polska -- 1945-1970.; Tczew (Polska) -- 1945-1970 -- druki ulotne